2020
DOI: 10.3390/cells10010043
|View full text |Cite
|
Sign up to set email alerts
|

Virion Secretion of Hepatitis B Virus Naturally Occurring Core Antigen Variants

Abstract: In natural infection, hepatitis B virus (HBV) core protein (HBc) accumulates frequent mutations. The most frequent HBc variant in chronic hepatitis B patients is mutant 97L, changing from an isoleucine or phenylalanine to a leucine (L) at HBc amino acid 97. One dogma in the HBV research field is that wild type HBV secretes predominantly virions containing mature double-stranded DNA genomes. Immature genomes, containing single-stranded RNA or DNA, do not get efficiently secreted until reaching genome maturity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…13 To date, this amino acid substitution, I97L, has been investigated in vitro. 16,[28][29][30][31][32] Yuan et al 16 analyzed the cell culture-generated HBV-I97L virus by density gradient and demonstrated that this virus mainly contains a SS HBV DNA genome, even in the enveloped virion in the HBsAg-rich fraction, although the HBV-wt virus in the same fraction predominantly contains a RC HBV DNA genome. Recently, Wu et al 31 investigated this amino acid substitution in vivo by using the mouse-hydrodynamic injection system of HBV molecular clones and suggested that HBV-I97L releases HBV virions with single-stranded genomes.…”
Section: Discussionmentioning
confidence: 99%
“…13 To date, this amino acid substitution, I97L, has been investigated in vitro. 16,[28][29][30][31][32] Yuan et al 16 analyzed the cell culture-generated HBV-I97L virus by density gradient and demonstrated that this virus mainly contains a SS HBV DNA genome, even in the enveloped virion in the HBsAg-rich fraction, although the HBV-wt virus in the same fraction predominantly contains a RC HBV DNA genome. Recently, Wu et al 31 investigated this amino acid substitution in vivo by using the mouse-hydrodynamic injection system of HBV molecular clones and suggested that HBV-I97L releases HBV virions with single-stranded genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) is an encapsulated, DNA-containing Pararetrovirus, which is one of the most successful pathogens in the world, and there is no radical cure for HBV infection at present [116]. As reported, late endosomes and MVB are used by HBV for assembly and release [117], and the budding and release of HBV virions are related to ESCRT-related molecules [116,[118][119][120]. For example, CD63 was found to co-locate with HBV protein in infected liver cells [117].…”
Section: Hbv and The Escrt Systemmentioning
confidence: 99%
“…Another highly popular concept is that core de-P could facilitate, or is required, for HBV virion secretion [ 44 , 52 ]. Using a biochemistry approach in a duck hepatitis B virus (DHBV) model, Pugh et al [ 44 ] compared HBc phosphorylation between the intracellular capsids and secreted extracellular virions.…”
Section: Introductionmentioning
confidence: 99%